CHARACTERZATION OF ENDOGENOUS BACTERIA AS POTENTIAL PROBIOTICS IN LARVAL REARING OF YELLOWFIN TUNA (Thunnus albacares) - Astuti, Ni Wayan Widya; Setiadi, Ananto; Gunawan, Gunawan; Hutapea, Jhon Harianto; Muzaki, Ahmad; Haryanti, Haryanti (Indonesian Aquaculture Journal, 2025)
The main objective of this study was to determine the profile of endogenous intestinal bacteria of yellowfin tuna, Thunnus albacares that can function as potential probiotics in the digestive system and used for the maintenance of yellowfin tuna larvae. Wild yellowfin tuna, T. albacares was collected from the waters of Gerokgak, Buleleng, North Bali, Indonesia. Intestinal bacteria were isolated, identified, characterized, and followed by enzymatic hydrolysis activity tests, antagonistic tests and pathogenicity tests to select candidate bacteria as probiotics. The results of the enzymatic hydrolysis activity test showed that there were 4 isolates of candidate probiotic bacteria that were active in enzymatic synthesis for amylase, lipase, casease, lecithinase, gelatinase. Identification through Sanger sequencing resulted in 4 potential bacterial isolates as probiotics, namely Bacillus subtillis strain T-A1, Bacillus amyloliquefaciens strain T-N2, Bacillus subtillis strain T-O4, and Paraclostridium bifermentans strain T-O6. These four bacteria were not antagonistic between varieties and were not pathogenic in Tuna fish. Yellowfin tuna fed probiotic supplements grew faster (5.5002 ± 0.2 mm) than the control (4.9002 ± 0.4 mm). The success of yellowfin tuna seed production is expected to be sustainable and its implementation in the private sector for aquaculture purposes.